The tale of Mrs. Tittlemouse - Potter, Beatrix; Verbae, Josh (Interactive Media London, 2015)
Once upon a time there was a wood-mouse, and her name was Mrs. Tittlemouse. She lived in a bank under a hedge. Such a funny house! There were yards and yards of sandy passages, leading to storerooms and nut-cellars and seed-cellars, all amongst the roots of the hedge